EFFECT OF CELLULAR MEMBRANE RESISTIVITY INHOMOGENEITY ON THE THERMAL NOISE-LIMIT (JOURNAL OF ADVANCES IN PHYSICS, 2015)
Our objective is to generalize the Weaver-Astumian (WA) and Kaune (KA) models of thermal noise limit to the case of cellular membrane resistivity asymmetry. The asymmetry of resistivity causes different effects in the two models. In the KA model, asymmetry decreases the characteristic field strength of the thermal limit over and increases it below the breaking frequency (10ï· ï€½ï´ mï€), while asymmetry decreases the spectral field strength of the thermal noise limit at all frequencies. We show that asymmetry does not change the character of the models, showing the absence of thermal noise limit at high and low frequencies in WA and KA models, respectively.